Expectations in Financial education in the light of primary research - Baranyi, Aranka; Csernák, József; Csiszárik-Kocsir, Ágnes (Acta Carolus Robertus, 2022)
The economic crisis of 2008 in Hungary drew attention to the important fact that improper financial decisions do not only entail risks for the individual or the household, but also aggregate losses for the whole economy can be the consequence of a bad financial decision. As a result of the financial and economic crisis, households previously indebted in euros, Swiss francs or even Japanese yen, had to pay up to 30-40% more than the original installment on their loans, while people lost their jobs and found themselves in a desperate situation. In retrospect, a generational shift is also needed to leave the bad experiences behind for the families affected. After years of difficulties, Hungarian households were soon faced with an unprecedented situation, where the familiar tools of economic governance and crisis management that used to work like "magic" no longer worked. At the beginning of 2020, within a few weeks, we were introduced to pandemics, COVID-19, masks, online education, home office and a list of other terms we had not previously known or used in our daily lives. In the following research we will give a brief summary of the performance of the national economy, followed by a discussion on the financial attitudes of households, and finally we will present the results of our own research, the key question of which is how respondents think about financial education today and what they expect from educators.